Loss of military equipment by the SADF at the Battle at Indungo during the Border War, 31 October 1987 - Scheepers, Marius; Pretorius, Fransjohan (Scientia Militaria - South African Journal of Military Studies, 2021)
This article takes the form of an investigation regarding the loss of military equipment by the South African Defence Force (SADF) at the Battle at Indungo, in an operation that was assigned the codename Operation Firewood, on 31 October 1987 during the Angolan Border War. The war was waged from 1966 to 1989 in Southern Africa. The case study of Operation Firewood illustrates some of the circumstances under which the SADF lost military equipment in Angola during the war. Operation Firewood was one of more than 300 SADF general operations201 that occurred in Angola. In the final stages of the war, the area north of Cuvelai provided the setting for the launching of Operation Firewood, some 285 kilometres north of the border with South West Africa/Namibia. The aim of this military operation was to eliminate an enemy base that housed elements of the People’s Liberation Army of Namibia (PLAN), the military wing of the South West Africa People’s Organisation (SWAPO).